Las especies vegetales raras y su volumen de hábitat en Santa Fe, Argentina - Camevale, Nélida Josefina (1994)
Habitat volume differences between rare and common plant species were compared in Santa Fe, Argentina. Rare species are those wruch are present in less lban 20% of quadrats. A principal component analysis showed that rare species fill habitat hiperspace volumes significantly smaller than common species.